Knowledge Management as an Aspect of the Intellectual Capital Management - Pshenychna, Liubov; Skyba, Olha (International Review of Management and Marketing, 2017)
The article describes the essence of the concept of knowledge management as an aspect of intellectual capital management, which serves as the main resource for improving of the company’s competitiveness and defines intellectual capital as an object of management. Managing intellectual capital, representing the company’s core value, contributes to achieving the company’s goals, creates the prerequisites for innovation, provides benchmarking in all activities, training and motivation of employees, increasing the efficiency of design, procurement and marketing processes, provides a fast pace of corporate development and implements the management process with maximum efficiency. Keywords: knowledge management, intellectual capital, competitiveness, pace of development, company image, professionalism, competence. JEL Classifications: D83, M1, O34